2020
DOI: 10.1016/j.jcmgh.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Tributyrin Inhibits Ethanol-Induced Epigenetic Repression of CPT-1A and Attenuates Hepatic Steatosis and Injury

Abstract: Healthy Liver or A enuated Steatosis Cons tu ve or Restored CPT-1A expression Suppressed CPT-1A expression Fa y Liver (Steatosis) p300 PGC1 p300 Transcrip onally Permissive Carni ne Palmitoyltransferase-1A (CPT-1A) Promoter Transcrip onally Repressive Carni ne Palmitoyltransferase-1A (CPT-1A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 61 publications
(88 reference statements)
0
29
0
Order By: Relevance
“…These findings were associated with amelioration of systemic glucose homeostasis (lower fasting glucose, an improved glucose tolerance and higher insulin sensitivity). These protective effects on the liver of obese mice together with the capacity of Tb to attenuate liver steatosis and injury in other experimental models [57][58][59] indicate that this organ is a key target of Tb. Indeed, after Tb administration, high concentrations of butyrate have been observed in the portal vein and liver [58].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…These findings were associated with amelioration of systemic glucose homeostasis (lower fasting glucose, an improved glucose tolerance and higher insulin sensitivity). These protective effects on the liver of obese mice together with the capacity of Tb to attenuate liver steatosis and injury in other experimental models [57][58][59] indicate that this organ is a key target of Tb. Indeed, after Tb administration, high concentrations of butyrate have been observed in the portal vein and liver [58].…”
Section: Discussionmentioning
confidence: 87%
“…These protective effects on the liver of obese mice together with the capacity of Tb to attenuate liver steatosis and injury in other experimental models [57][58][59] indicate that this organ is a key target of Tb. Indeed, after Tb administration, high concentrations of butyrate have been observed in the portal vein and liver [58]. This SCFA can then act directly on hepatocytes, as demonstrated by a recent study [58], inhibiting histone deacetylases (HDACs) and, consequently, affecting the expression of important genes for hepatic function, such as carnitine palmitoyltransferase-1 (CPT-1A).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Supplementation with saturated long-chain fatty acids (LCFAs) positively affected EtOH-mediated alterations in the intestinal barrier and gut microbiota dysbiosis 11 . It has been shown that tributyrin, a triglyceride found in butter and margarine, prevents alcohol-induced tight-junction (TJ) disruption, which in turn protects against intestinal hyperpermeability 12 . Various dietary fatty acids also differentially modulate EtOH-induced changes in the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Cellular and Molecular Gastroenterology and Hepatology, building on their own group's earlier reports, Donde et al 6 present novel findings that chronic alcohol induces histone Histone H3 Lysine 9 (H3K9) deacetylation in the promoter region of the fatty acid oxidation gene, carnitine palmitoyltransferase-1A (CPT-1A), indicating a closed or repressive chromatin state and hence reduced CPT-1A gene expression in alcoholic steatotic livers.…”
mentioning
confidence: 96%